Implementasi Sistem Zonasi Sebagai Upaya Pemerataan Peserta Didik Baru Pada SMP Negeri 01 Sekadau Hilir Dan SMP Negeri 10 Sekadau Hilir Kabupaten Sekadau - Fran Dawal (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study, titled “Implementation of the Zoning System as an Effort to Promote Equity in New Student Admissions at SMP Negeri 1 Sekadau Hilir and SMP Negeri 10 Sekadau Hilir, Sekadau Regency,” aims to analyze the implementation of the 2024/2025 PPDB (New Student Admissions) zoning system based on George C. Edwards III’s policy implementation model—which encompasses communication, resources, the disposition of implementers, and bureaucratic structure—and to evaluate its contribution to promoting educational equity. The research employed a qualitative method with a descriptive approach, using interviews, observations, and document analysis as data collection techniques.The findings reveal that communication at SMP Negeri 1 Sekadau Hilir was more effective due to the use of both online and offline communication channels, whereas SMP Negeri 10 Sekadau Hilir relied primarily on face-to-face interactions. Resources at SMP Negeri 1 Sekadau Hilir were relatively sufficient, while those at SMP Negeri 10 remained limited. The implementers in both schools demonstrated positive dispositions, although they applied different strategies in carrying out the policy. The bureaucratic structure in both institutions was supported by the Zoning Decree (SK Zonasi) and the PPDB Committee Decree (SK Panitia PPDB), which provided formal guidance for the implementation process.The PPDB outcomes show that SMP Negeri 1 Sekadau Hilir successfully fulfilled its quota of 320 students, with the majority admitted through the zoning pathway. In contrast, SMP Negeri 10 Sekadau Hilir admitted only 64 students (two classes), all of whom were accepted through the zoning pathway. These findings confirm that the zoning policy has been implemented in accordance with existing regulations; however, educational equity has not been fully achieved due to disparities in resources and accessibility between the two schools.